Behavioral Phenotypes of Foxg1 Heterozygous Mice - Younger, Skyler; Boutros, Sydney; Cargnin, Francesca; Jeon, Shin; Lee, Jae W.; Lee, Soo-Kyung; Raber, Jacob (Frontiers in Pharmacology, 2022)
FOXG1 syndrome (FS, aka a congenital variant of Rett syndrome) is a recently defined rare and devastating neurodevelopmental disorder characterized by various symptoms, including severe intellectual disability, autistic features, involuntary and continuous jerky movements, feeding problems, sleep disturbances, seizures, irritability, and excessive crying. FS results from mutations in a single allele of the FOXG1 gene, leading to impaired FOXG1 function. Therefore, in establishing mouse models for FS, it is important to test if heterozygous (HET) mutation in the Foxg1 gene, mimicking genotypes of the human FS individuals, also manifests phenotypes similar to their symptoms. We analyzed HET mice with a null mutation allele in a single copy of Foxg1, and found that they show various phenotypes resembling the symptoms of the human FS individuals. These include increased anxiety in the open field as well as impairment in object recognition, motor coordination, and fear learning and contextual and cued fear memory. Our results suggest that Foxg1 HET mice recapitulate at least some symptoms of the human FS individuals.